An Experimental Application of the DELPHI Method to the Use of Experts - Dalkey, Norman; Helmer, Olaf (Management Science, 1963)
This paper gives an account of an experiment in the use of the so-called DELPHI method, which was devised in order to obtain the most reliable opinion consensus of a group of experts by subjecting them to a series of questionnaires in depth interspersed with controlled opinion feedback.